Comammox bacteria predominate among ammonia-oxidizing microorganisms in municipal but not in refinery wastewater treatment plants. (15th August 2022) - He, Shishi; Zhao, Zhirong; Tian, Zhichao; Xu, Chi; Liu, Yuan; He, Da; Zhang, Yinghui; Zheng, Maosheng
Abstract: Comammox bacteria have proved to be one dominant and significant ammonia-oxidizing microorganisms (AOMs) in municipal wastewater treatment plants (WWTPs), however, it still remains unknown about their abundance and diversity in industrial WWTPs. In this study, activated sludge samples from 8 municipal WWTPs and 6 industrial WWTPs treating refinery wastewater were taken and analyzed using qPCR and amoA gene sequencing. Intriguingly, quantitative real-time PCR (qPCR) results suggested that comammox bacteria had a higher numerical abundance compared with ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) in municipal WWTPs but did not in refinery WWTPs. Moreover, comammox amoA sequences obtained from high-throughput sequencing were retrieved from all the 8 municipal samples but only 1 industrial sample. Further phylogenetic analysis revealed that N. nitrosa cluster accounted for as high as 79.56% of the total comammox affiliated sequences, which was the most numerically abundant comammox species in municipal WWTPs. This study provided new insights into the abundance and diversity of comammox bacteria in the biological nitrification process in municipal and refinery wastewater treatment systems. Graphical abstract: Image 1 Highlights: Comammox bacteria predominated numerally in wastewater treatment plants (WWTPs). Comammox amoA accounted for 16.7% of the three amoA sequences in refinery WWTPs. N. nitrosa was the dominant comammox species in municipal WWTPs. N. nitrificans sister was the dominant comammox species in a refinery WWTP.